Gender Dalam Tinjauan Sufisme sebagai Konsep Kesetaraan Feminim dan Maskulin Melalui Pendekatan Spiritual - Abdul Jalil; St. Aminah Azis (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2019)
The perfection of every human being can be achieved if he is able to harmonize the properties of Jalal and Jamal in himself harmoniously, while the perfection of human beings is achieved if men and women can integrate themselves in a harmonious whole both in the narrow sense (marriage) and in the broad sense , namely the occurrence of harmonious relations between men and women in various aspects of life. The concept of masculine and feminine is not necessary and should not be opposed because both are equally important and equally noble. Thus the Sufis give an esoteric interpretation so that they must be fixated on their spiritual increase in God without having to look at His masculine and feminine sides of God, they concentrate on reaching His Jalal and Jamal God together. When they have reached a high spiritual level, they are truly sincere to God so that in all their actions and behavior there is not the slightest spark of worldly interest as is characteristic of humans in general. Functional relations as the basis of humanity "wa‘ ala ar-rijal ‘alaihinna darajah" is for men equals above women and when both are united it will become a real human, and the elaboration of both is the perfection of reaching perfection.